(3GdGbJOG aj eYQaI Gdhba hGdGHJOGs - (3YHO Gddg Hf eMeO Hf YHO Gddg Hf CHj RjO GdCfUGQj eYjf GdOjf Hf GdfcRGQj, CHh eMeOs
(3ChdgG (B:s
(3hHYO abO QZH Edi LeGYI ef GdeTJZdjf HJdGhI GdbQBf eeG jJYdb HGdhba hGdEHJOGA s
(3BNQgG (B:s
(3hGdJeGe BNQ GdShQI hbO Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3bQGAGJ (B122) s
Keywords: (3GdbQGAGJ hGdJLhjOs